2012
DOI: 10.1177/0022034511434055
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Regulatory Mechanisms of Tongue Myogenesis

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental. AbstrActThe tongue exerts crucial functions in our daily life. However, we know very little about the regulatory mechanisms of mammalian tongue development. In this review, we summarize recent findings of the molecular and cellular mechanisms that control tissue-tissue interactions during tongue morphogenesis. Specifically, cranial neural crest cells (CNCC) lead the initiation of tongue bud formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 59 publications
2
78
0
1
Order By: Relevance
“…However, these theories do not seem to take into account the normal development of the tongue and the multipotent capacity of the CNC derived cells which are primarily involved in this process. Normally, the tongue starts to develop at the end of the fourth week with the formation of multiple swellings on the floor of the pharynx, which are produced by cells that migrate from the CNC into the branchial arches, in particular the first one [32]. During and after migration, these cells contribute to the development of most of the craniofacial structures, generating, based on the effect of specific genetic and epigenetic factors and according to a hierarchical model of lineage segregation, a very wide range of ectomesenchymal and neural derivatives [33,34,35,36,37,38,39,40,41,42,43,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these theories do not seem to take into account the normal development of the tongue and the multipotent capacity of the CNC derived cells which are primarily involved in this process. Normally, the tongue starts to develop at the end of the fourth week with the formation of multiple swellings on the floor of the pharynx, which are produced by cells that migrate from the CNC into the branchial arches, in particular the first one [32]. During and after migration, these cells contribute to the development of most of the craniofacial structures, generating, based on the effect of specific genetic and epigenetic factors and according to a hierarchical model of lineage segregation, a very wide range of ectomesenchymal and neural derivatives [33,34,35,36,37,38,39,40,41,42,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…ly, in the tongue, these cells normally provide to the generation of the ectomesenchymal cell populations (connective tissue cells, smooth muscle cells, and vasculature) that a) act as a scaffold for the myogenic progenitors migrating from the occipital somites and b) provide the molecular instruction to direct their survival, proliferation, and differentiation towards the lingual muscles [32]. Thus, based on the role of CNC-derived cells in the normal tongue organogenesis and on their multipotent differentiation capacity, glial choristoma of the tongue may be reasonably re-thought as the result of a normal, but heterotopic, differentiation toward neural derivatives of the migratory or post-migratory CNC-derived cells involved in the generation of the ectomesenchymal anlagen of the tongue.…”
Section: F Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic labeling experiments have shown that the mesoderm-derived myogenic progenitors primarily occupy the core of the tongue primordium, whereas the CNC-derived cells largely contribute to the region that surrounds the myogenic core as well as the tongue septum (21). Interactions between these two groups of cells are essential for tongue development, and TGF␤-mediated FGF signaling plays a critical role in such tissue-tissue interactions (21,24).…”
mentioning
confidence: 99%
“…The tongue is composed of intrinsic (situated within the tongue) and extrinsic (originating outside the tongue) muscles and has the capacity for complicated movements due to the muscles' unique feature of having only one end tethered to bony structures. CNC cells give rise to tenocytes and fibroblasts that overlie the muscle fibers and provide the connective tissue in the tongue (4,5). Twenty-two medical syndromes, including acrorenal mandibular syndrome, aglossiaadactylia syndrome, and Freeman-Sheldon syndrome, among others, exhibit microglossia without muscular defects in the rest of the body (6).…”
mentioning
confidence: 99%